Pengujian Pengalaman Pengguna pada Sistem Informasi Pengelolaan Keuangan dan Inventaris Barang Menggunakan User Experience Questionnaire (UEQ) - Aliyah, Aliyah; Hartono, Nahrun (Subaltren Inti Media, 2025)
User experience testing is an essential step in evaluating the quality of user interaction with an information system. This study aims to analyze the user experience of a financial management information system using the User Experience Questionnaire (UEQ) method. This method covers six main evaluation dimensions: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The evaluation results indicate that the financial management information system performs positively across all dimensions, with the following average scores: Attractiveness 1.91, Perspicuity 2.22, Efficiency 1.77, Dependability 1.94, Stimulation 1.78, and Novelty 1.89. The highest score in the Perspicuity dimension shows that the system is easy to understand and use by users. Meanwhile, the scores in the Efficiency, Stimulation, and Novelty dimensions provide insights for improving the system’s optimization, appeal, and innovation. Overall, these results demonstrate that the user experience of the financial management information system falls into the positive category and supports the system’s effectiveness in helping users manage finances efficiently. Further development recommendations focus on enhancing the efficiency and stimulation dimensions to provide a better user experience.